Glomerular filtration barrier dysfunction in a self-limiting, RNA virus-induced glomerulopathy resembles findings in idiopathic nephrotic syndromes - Nußhag, Christian; Stütz, Alisa; Hägele, Stefan; Speer, Claudius; Kälble, Florian; Eckert, Christoph; Brenner, Thorsten; Weigand, Markus A.; Morath, Christian; Reiser, Jochen; Zeier, Martin; Krautkrämer, Ellen (Scientific reports, 2020)
Podocyte injury has recently been described as unifying feature in idiopathic nephrotic syndromes (INS). Puumala hantavirus (PUUV) infection represents a unique RNA virus-induced renal disease with significant proteinuria. The underlying pathomechanism is unclear. We hypothesized that PUUV infection results in podocyte injury, similar to findings in INS. We therefore analyzed standard markers of glomerular proteinuria (e.g. immunoglobulin G [IgG]), urinary nephrin excretion (podocyte injury) and serum levels of the soluble urokinase plasminogen activator receptor (suPAR), a proposed pathomechanically involved molecule in INS, in PUUV-infected patients. Hantavirus patients showed significantly increased urinary nephrin, IgG and serum suPAR concentrations compared to healthy controls. Nephrin and IgG levels were significantly higher in patients with severe proteinuria than with mild proteinuria, and nephrin correlated strongly with biomarkers of glomerular proteinuria over time. Congruently, electron microcopy analyses showed a focal podocyte foot process effacement. suPAR correlated significantly with urinary nephrin, IgG and albumin levels, suggesting suPAR as a pathophysiological mediator in podocyte dysfunction. In contrast to INS, proteinuria recovered autonomously in hantavirus patients. This study reveals podocyte injury as main cause of proteinuria in hantavirus patients. A better understanding of the regenerative nature of hantavirus-induced glomerulopathy may generate new therapeutic approaches for INS.